Slidable and Highly Ionic Conductive Polymer Binder for High‐Performance Si Anodes in Lithium‐Ion Batteries. Issue 6 (23rd December 2022) - Cai, Yifeng; Liu, Caixia; Yu, Zhiao; Ma, Wencan; Jin, Qi; Du, Ruichun; Qian, Bingyun; Jin, Xinxin; Wu, Haomin; Zhang, Qiuhong; Jia, Xudong
Abstract: Silicon is expected to become the ideal anode material for the next generation of high energy density lithium battery because of its high theoretical capacity (4200 mAh g −1 ). However, for silicon electrodes, the initial coulombic efficiency (ICE) is low and the volume of the electrode changes by over 300% after lithiation. The capacity of the silicon electrode decreases rapidly during cycling, hindering the practical application. In this work, a slidable and highly ionic conductive flexible polymer binder with a specific single‐ion structure (abbreviated as SSIP) is presented in which polyrotaxane acts as a dynamic crosslinker. The ionic conducting network is expected to reduce the overall resistance, improve ICE and stabilize the electrode interface. Furthermore, the introduction of slidable polyrotaxane increases the reversible dynamics of the binder and improves the long‐term cycling stability and rate performance. The silicon anode based on SSIP provides a discharge capacity of ≈1650 mAh g −1 after 400 cycles at 0.5C with a high ICE of upto 92.0%. Additionally, the electrode still exhibits a high ICE of 87.5% with an ultra‐high Si loading of 3.84 mg cm −2 and maintains a satisfying areal capacity of 5.9 mAh cm −2 after 50 cycles, exhibiting the potential application of SSIP in silicon‐based anodes. Abstract : A highly ionic conductive polymer binder with molecular dynamics is designed and exhibits both excellent mechanical performance and satisfactory electrochemical properties. Based on the novel multi‐functional binder, the silicon anode shows reliable performance with a high ICE and reliable performance.